Paradoksy teorii rosyjskiej (nie)współczesności? Iwana Jesaułowa koncepcja mitologicznej dominanty w strukturach postsowieckiej codzienności .......... 367 - Broda, Marian (Czas w kulturze rosyjskiej, 2019)
PARADOXES OF THE RUSSIAN NON-CONTEMPORANEITY THEORY? IVAN ESAULOV’S CONCEPT OF A MYTHOLOGICAL DOMINANT IN THE STRUCTURES OF POST-SOVIET EVERYDAY LIFEThe way of understanding the world, Russia, time, and history presented by Ivan Esaulov is characterized by the co-presence of the subjective intention of radical distancing from the Russian previousness and from a range of content typical of the mentality and intellectual-cultural tradition of Russians, co-determining the nature of their history and presence. The realisation of the above seems to be important for the analysis of both the Esaulov’s concept and the objectivity that it serves to explain. The presence of the mythological dominant in the structures of post-Soviet everyday life, which he emphasizes, turns out not to be the theory of non-contemporaneity of the post-Soviet Russia, but de facto a postulate, and not empirically verifiable, descriptive theory of the alleged non-Russianhood of the past contemporaneity. Thus, not only Esaulov’s – and likewise thinking people’s – premises of objective belief in the possibility of the desired transformation of Russia become more understandable, but also the mechanisms of systemic self-reproduction-continuation of the Russian previousness, undermining the feasibility of this transformation.